The capability of Village’s Administration in the Implementation of an Effective Village Consultative Meeting Following the Indonesian Government’s Regulation (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2020)
One of the characteristics of Indonesian democracy is a mechanism in decision-making through a forum of discussion. The village, that stands as the lowest unit of the governance system, is also required to hold the meeting called Musyawarah Desa (village meeting). The meeting is organized following the standard and provisions in the Regulation of Minister of Village and Transmigration Affairs No. 2 of 2015 on the Procedures and Mechanism in Decision-Making in Village Meeting (Pedoman Tata Tertib dan Mekanis-me Pengambilan Keputusan Musyawarah Desa). This writing is based on the information on the capability of the village government in organizing the effective village meeting. The effectiveness of village meeting can be indicated by the elements of society that are involved in the meeting, the preparation of the meeting, procedures of organizing the village meeting and the mechanism of the meeting, which are all mentioned in the Regulation of Minister of Village and Transmigration Affairs No. 2 of 2015 on the Procedures and Mechanism in Decision-Making in Village Meeting. This research uses qualitative methods. The result shows that the village meeting has been organized effectively, in which all aspects required in the regulation has been followed. Despite being effective, six factors obstruct the process, which the village administration have to be solved to get more quality meeting.